Resistance of Eleusine indica to non-selective herbicides in Indonesian oil palm plantation - UUM UMIYATI; DENNY KURNIADIE; RYAN WIDIANTO; DEDI WIDAYAT; CEPPY NASAHI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Umiyati U, Kurniadie D, Widianto R, Widayat D, Nasahi C. 2023. Resistance of Eleusine indica to non-selective herbicides in Indonesian oil palm plantation. Biodiversitas 24: 4661-4667. Indonesia is the world's largest producer of oil palm. One biological constraint that may reduce the national oil palm production is Eleusine indica (L.) Gaertn (goosegrass). This weed is usually controlled chemically using non-selective herbicides, such as glyphosate, paraquat, and ammonium glufosinate. Although these herbicides are widely used, there are minimal case reports of weed resistance in Indonesia. This study aimed to map and quantify the herbicide resistance of goosegrass in Indonesian oil palm plantations. Weed mortality after herbicide application was used to determine the resistance. The study collected samples from Indonesia's six primary oil palm regions: West Sumatra, North Sumatra, Riau, Lampung, Belitung, and West Kalimantan. The sample collection process was supplemented by conducting interviews to get information on the herbicide application practices of palm oil growers. The results showed that 15 samples of goosegrass from various locations were resistant to glyphosate, 17 were resistant to paraquat, and one showed developing resistance to ammonium glufosinate. The most resistant goosegrass was found in North Sumatra, with a resistant index of 3.32 and 3.81 to glyphosate and paraquat, respectively. At the same time, the resistance to ammonium glufosinate could not be measured because the low doses of ammonium glufosinate were sufficient to control the weeds.